Hydrogen production in anaerobic continuous flow reactor using crude glycerol from biodiesel production - Adames, Luan Vieira [UNESP]; Pires, Lorena Oliveira [UNESP]; Tallarico Adorno, Maria Angela; Maintinguer, Sandra Imaculada [UNESP] (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2021)
The depletion of oil reserves and the growing concern about climate change have accelerated new research to obtain renewable energy. The production of biogas through anaerobic digestion has proved to be a great option, not only for energy production, but also for the proper management of organic waste. Biodiesel had its production increased in several countries as it is a renewable and biodegradable fuel; moreover, it does not require major modifications for its use in diesel engines. However, it is largely obtained from the transesterification of vegetable oils and animal fat, where its yield is 9 volumes of biodiesel to 1 volume of glycerol. The crude glycerol has a low degree of purity, becoming an inexpensive raw material with the potential to produce renewable energy, mainly hydrogen gas (H-2) and methane (CH4). In this sense, the objectives of this study were: to operate a horizontal anaerobic reactor with fixed bed (HARFB), with continuous feeding and to determine its start in the production of H-2 from residual biodiesel glycerol co-digested in sanitary sewage in the phases from: Startup, Test 1 and Test 2. During the Startup and Test 1 assay, the affluent was constituted by 99% sewage 1% crude glycerol (v/v) and 1.5% crude glycerol in Test 2. At Startup and Test 1, production averages of 1 mol H-2 m(3) d(-1) and 3.2 moles H-2 m(3) d(-1) were verified, respectively. The highest daily production achieved was 11.34 moles H-2 m(3) d(-1) in Test 2 with an average generation of volatile fatty acids (VFA) of 3414.0 mg L-1. Such results were promising and new advances with higher proportions of crude glycerol and buffering agents could avoid large pH variations, thus enabling higher and more stable generations of H-2 in continuous reactors.
Keywords: Biogas; Sanitary sewage; Continuous Reactor